Occurrence Study of Rubella Virus in Miscarriages' Women in Al-Diwanyah Province - Aqeel Abbas Kareem (Al-Qadisiyah Journal of Pure Science, 2017)
A total of 500 samples of patients which collected from miscarriages' women( aborted women) 134 were positive for rubella in percentage of (26.8%) and 100 of healthy as control group. Enzyme linked Immunosorbent Assay (ELISA) were used to assess the presence of specific antibodies against the virus. 1 (0.75) were positive for IgM antibody and 113 (84.33 %) for IgG. Whereas all control group 100 have been found to be negative. The occurrence of the pathogen in relation to the residence, age and occupation has been studied. This study was conducted to detect the possible associationbetween the infection and miscarriages at the Children Maternity Hospital andprivate laboratories in Al-Diwaniya Province during the period from July2012 to March 2013.the highest ratio of infection in the first trimester at agegroup (21-30) years. Miscarriages' women were classified according to differenttrimesters and number of gravidity